A method for evaluating and principles for developing a map of the productive potential of agricultural land - Podciborski, Tomasz (International Conference “Environmental Engineering”, 2017)
Crop production is a highly complex process. It requires comprehensive knowledge about natural phenomena and agronomic treatments that provide plans with optimal conditions for growth and development. Crop yield is influenced by a variety of environmental factors, including availability of water, temperature and light. The main anthropogenic element in crop production is the shape of the plot which is determined by the land division plan. Farmers also have to undertake the relevant measures to ensure the appropriate soil pH, soil structure, nutrient content and microbial activity. The main objective of this study was to develop a method and principles for evaluating the productive potential of agricultural land, and to compile a map presenting the productive potential of agricultural land. The main aim was achieved through detailed goals. Model evaluation indicators and criteria, the sources of information used in the evaluation process as well as the stages of and principles for developing a map of the productive potential of agricultural land were described. The results of an evaluation performed on a selected research site were presented in graphical form in the Conclusions section.
Keywords: farmland protection; productive potential of land; agricultural land